Lookback procedures after postdonation notifications during a Q fever outbreak in the Netherlands. Issue 4 (13th July 2012) - van Kraaij, Marian G.J.; Slot, Ed; Hogema, Boris M.; Zaaijer, Hans L.
<x xml:space="preserve">Abstract</x> BACKGROUND: Since 2007, large outbreaks of Q fever occurred in the Netherlands. The unprecedented number of Q fever infections resulted in the need for the Dutch blood transfusion service to evaluate the risk of transmission of Coxiella burnetii via blood. STUDY DESIGN AND METHODS: A lookback procedure (recipient tracing) was performed for transfused blood products of whole blood donors with confirmed C. burnetii infection within 3 weeks before to 3 weeks after blood donation. Repository samples of index donations were tested with real‐time polymerase chain reaction (PCR) for C. burnetii DNA. Hospitals were asked to review the medical records of recipients and—if considered necessary—to test the recipients for infection with C. burnetii. RESULTS: From 2007 through 2011, a total of 33 blood donors notified the blood bank of infection with C. burnetii. Thirteen donations fulfilled the criteria for a lookback procedure (18 blood products). C. burnetii PCR was positive in 1 of 13 repository samples of index donations. Blood products were transfused to 18 recipients. Information was retrieved from 12 of them; seven were tested for C. burnetii. Two recipients showed positive serology. However, transmission of C. burnetii via transfusion was unlikely, especially since most recipients lived in the same Q fever–affected area as the donors. CONCLUSION: Blood donors who have clinical Q fever around the time of blood donation are unlikely to test positive for C. burnetii by PCR in repository samples. Transmission of C. burnetii via transfusion of blood products could not be demonstrated in a lookback exercise.